NGOS IN THE FIELD OF POLITICS OF MEMORY: REGIONAL DIMENSION (comparative analysis of Lviv, Ivano-Frankivsk and Ternopil regions) - Венгринюк, Л. Я. (PRECARPATHIAN BULLETIN OF THE SHEVCHENKO SCIENTIFIC SOCIETY Idea, 2019)
The article analyzes regional NGOs in the field of politics of memory. Presented its expanded classification that distinguishes NGOs organized by living witnesses, victims or members of certain events in the past, or in memory of the victims of the tragic historical realities; NGOs, whose activities are focused on the protection and restoration of certain traditions, saved by public memory; scientific, cultural and educational organizations whose activities are focused on the study and promotion of knowledge about the past, research and discovery of still unknown pages of history; modern NGOs which, having broader programmatic principles involved in its activities to the problems of memory, commemoration key historical dates and promotion objectively highlight the historical past; NGOs created by representatives of national minorities. The comparative analysis of associations of Lviv, Ivano-Frankivsk and Ternopil regions is carried.